1987
DOI: 10.1123/ijsb.3.4.326
|View full text |Cite
|
Sign up to set email alerts
|

Ski Boots: Biomechanical Issues Regarding Skiing Safety and Performance

Abstract: In a state-of-the-art paper on skiing performance and on skiing safety, aspects of ski boot design are discussed. The influence of ski boots on the skier-bootbinding-ski system is described, and suggestions are made about improving ski boots regarding better skiing performance, less inadvertent binding releases, and less lower extremity equipment related injuries. The design of the boot sole and the boot shaft with its influence on binding release values is particularly described. Furthermore, in the forward l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…These alterations led to the hypothesis that some ankle orthoses may reduce the ability of the ankle to absorb energy, and thereby increase the dissipation demands of the knee and hip joints. 28 This hypothesis parallels the speculation that the effective protection of the lower leg and ankle by ski boots promotes direct translation of the forces to the knee, 22 thereby explaining the high incidence of knee injury in skiers.…”
mentioning
confidence: 65%
“…These alterations led to the hypothesis that some ankle orthoses may reduce the ability of the ankle to absorb energy, and thereby increase the dissipation demands of the knee and hip joints. 28 This hypothesis parallels the speculation that the effective protection of the lower leg and ankle by ski boots promotes direct translation of the forces to the knee, 22 thereby explaining the high incidence of knee injury in skiers.…”
mentioning
confidence: 65%
“…A fall in this position is usually the result of the skier's poor technique on entering a jump and on landing. 6,18 Thirdly, overconfident skiers tend to select very difficult slopes despite their poor technical abilities. Also, less safety-conscious skiers tend to ignore their fatigue and other extrinsic factors such as the weather or the slope condition.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, ACL skiing injuries were frequently reported to be related to LEER injuries, and in particular, to the functional failure of the ski bindings. 2,[4][5][6][7][8][9]12,15,17,22 However, the influence of other factors, such as the skier's physical condition, the course difficulty, and the slope conditions, have been, unfortunately, underestimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of anterior cruciate ligament (ACL) injuries in Alpine skiing has increased in the past 2 decades (Bechtel, Ellman, & Jordon, 1984;Feagin et al, 1987;Hauser & Schaff, 1987;Howe & Johnson, 1982;Johnson, Ettlinger, & Shealy, 1991;McConkey, 1986). This increase has been associated at least partly with changes in the design of ski boots and the design and release settings of bindings (Bally, Boreiko, Bonjour, & Brown, 1989;Figueras et al, 1987;Johnson, Ettlinger, Campbell, & Pope, 1980;Johnson, Ettlinger, & Shealy, 1989;Johnson et al, 1991).…”
mentioning
confidence: 99%